Is it feasible to produce iron ore in Nigeria via local foundry for spare parts? A cost-benefit and net present value analysis - Edeme, Richardson Kojo; Osemenam, Victor Victor (Universitas Negeri Malang, 2019)
In the wake of Nigeria?s desire to diversify and the move to revive iron ore deposit, various options are considered on how best to produce iron ore at the least cost possible. This study evaluates plausible source of spare parts for earth moving equipment and establishment of local foundry to forge spare parts utilized for iron ore production. The benefit-cost and net discounted present value analysis were employed and findings shows that both sources are not profitable to the entity?s operation as it increases running expenses, amid a 16 percent inflation rate, an unfavorable global market exchange rate of 1 to N359.201 and a non-profitable global market price of 62.59 (N22, 482) within projection of 5 years which is very critical to the revival of the nation?s iron ore deposit. The policy suggestion from the findings is that new price higher than the current global market price be set in order to absorb current cost accruable to the entity at 16 percent inflationary rate and a global market exchange rate.